Unveiling key drivers of industry 4.0 adaptation in CKD automotive manufacturing companies : evidence from asia and south america - Norhana, Mohd Aripin; Mezhuyev, Vitaliy I.; Nawanir, Gusman; Muhammad Fakhrul, Yusuf; Nor Rokiah Hanum, Md Haron (Institute of Electrical and Electronics Engineers Inc., 2023)
The paper investigates the drivers of Industry 4.0 adaptation in the CKD automotive industry. The methodology is based on a cross-sectional empirical study, where the samples were drawn using simple random sampling. Four hypotheses were developed, and the data were collected using an online survey and a standardised questionnaire. Survey responses were received from white-collar employees at a CKD automotive manufacturer encompassing multiple CKD plants in Asia and South America. One hundred fifty survey responses were received and next analysed using Structural Equation Modelling (SEM) in SmartPLS software. Based on the findings, three drivers, namely, business competitiveness, customer satisfaction, and operational improvement, positively affect the Industry 4.0 adaptation in CKD manufacturing companies. However, the financial benefit factor does not affect the adaptation of Industry 4.0 in manufacturing industries. This study contributes to the existing knowledge in understanding the drivers for Industry 4.0 adaptation. In addition, these findings might aid the practitioners and government in tailoring the policy related to Industry 4.0 in CKD automotive manufacturing industries.